Comprehensive exploration of research and publication endeavours among Universiti Teknologi MARA academicians - Tarmuji, Nor Habibah; Mohamad Adnan, Noor Izyan; Abu Hassan, Nurul Nadiya; Mohamed, Norhuda; Razali, Fadila Amira; Mohd Shohaimi, Norshahidatul Akmar; Wan Abdul Rahman, Wan Mohd Nazri (GADING Journal for the Social Sciences, 2025)
A study was conducted to investigate the research and publication activities of lecturers at various UiTM branches. The study aimed to evaluate the accomplishments of lecturers in research and publication activities and to identify any challenges they encountered. A total of 247 respondents participated in this study. Descriptive statistics were utilised to explore the data for each variable, which included the use of pie and bar charts. The findings indicated that 57% of respondents are currently involved in active grants, either as principal investigators or team members. However, the majority of respondents (60%) are not engaged in collaborations with external higher education institutions, whether public or private. Additionally, a majority of respondents do not have access to international and industry grants, with 95% and 79% lacking these, respectively. Moreover, 56% of respondents have never supervised postgraduate students. Furthermore, 66% and 51% of respondents have publications indexed in Scopus/WoS and MyCite/ERA, respectively. Finally, 74% of respondents agreed that the main obstacle to becoming a lead author is being preoccupied with teaching and learning responsibilities. However, the majority of respondents, 77% and 55% respectively, are satisfied with their teaching and learning achievements and the support provided by UiTM to enhance research and publication activities. Thus, it is suggested that UiTM consider implementing workload adjustments, research leave, or time management support to assist lecturers in balancing their teaching, research, publication activities, and administrative responsibilities.